The Foundation of International Humanitarian Law Enforcement: State Obligations to Respect and to Ensure Respect - rezvan bagherzadeh; amir hossein ranjbarian (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
International Humanitarian Law is considered as a legal regime whose governing rules are being changed particularly as a result of the transformation of international and non-international armed conflicts. But noticeably, the stability of humanitarian law enforcement has more or less constantly survived. In other words, nearly all states feel to have an obligation to adhere strictly to the rules, which reflects in common article 1 of 1949 Geneva conventions and some consequent Protocols. It reads: “The High Contracting Parties undertake to respect and to ensure respect for the present Convention [this Protocol] in all circumstances.” Accordingly, there are many areas in which all parties should establish and anticipate sufficient actions and mechanisms e. g. passing some Acts and Regulations, instructing military forces how to act, and punishing the perpetrators of certain crimes for their commission. Presently, to respect and ensure respect are undoubtedly applicable on varying entities beside states. This article proceeds to discuss the common article and some challenging dimensions.